Three dimensional temperature field of thermoelectric radiant panel system: Analytical modeling and experimental validation. (November 2017) - Luo, Yongqiang; Zhang, Ling; Liu, Zhongbing; Wu, Jing; Zhang, Yelin; Wu, Zhenghong
Highlights: Three-dimensional analytical model of thermoelectric radiant system is established. The system model is validated by experiments under steady and dynamic state. The simulation differences of 2-D and 3-D model are numerically compared. Abstract: Thermoelectric radiant panel (TERP) system is a new prototype of radiant system with fast cooling/heating speed, stable operation, and easier system control. The full and deeper understanding of heat transfer of TERP could be beneficial for system design, operation and control. The purpose of this paper is to establish a three-dimensional analytical model of TERP in both steady and dynamic state which could be used as a useful tool for further research. The method of mirror virtual heat sources was adopted to transform original heat conduction problem to the superposition of temperature solutions of radiant panel in infinite plane. In addition, this method can offer a highly flexible treatment on boundary conditions. The basic conduction problem was solved by the method of separation of variables and the temperature field subjected to non-functional finite-plane heat source was modeled by Duhamel theorem in simulation algorithm. Thermal network RC model for TEM and copper cube was integrated with the analytical model of radiant panel for simulation of TERP. The simulation accuracy of three-dimensional temperature field of TERP was verified by comparing with experimental results in both steady and dynamic state. In order to understand the simulation difference between the previous 2-D and new 3-D model, a comparative study was implemented under different model parameters arrangements. This numerical comparative investigation can provide a basic guidance on the application of 2-D and 3-D model. And this study offered a solid and sophisticated system model for TERP.